2021
DOI: 10.1186/s12891-021-04545-6
|View full text |Cite
|
Sign up to set email alerts
|

Combined serum and synovial C-reactive protein tests: a valuable adjunct to the diagnosis of chronic prosthetic joint infection

Abstract: Background Diagnosis of periprosthetic joint infection (PJI), especially chronic PJI, is very confusing and challenging. The value of C-reactive protein (CRP) in infectious diseases has been recognized, but the diagnostic value of CRP in chronic PJI is unknown. Our aim was to investigate the diagnostic value of synovial CRP in chronic PJI and to explore the role of combined serum and synovial CRP in distinguishing chronic PJI from aseptic failure after knee and hip arthroplasties. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…The development of a PJI prolongs the inpatient stay considerably [31,32]. The maximum CRP and the presence of a second peak can be helpful for early infection detection [33][34][35]. This study was able to demonstrate the clinical applicability of two formulas forecasting a PJI.…”
Section: Discussionmentioning
confidence: 72%
“…The development of a PJI prolongs the inpatient stay considerably [31,32]. The maximum CRP and the presence of a second peak can be helpful for early infection detection [33][34][35]. This study was able to demonstrate the clinical applicability of two formulas forecasting a PJI.…”
Section: Discussionmentioning
confidence: 72%
“…1, and the QUADAS‐2 score criteria revealed that most of the extracted studies had high risks. Excluding brand new markers that only appeared recently and have limited data, 129 records reported diagnostic information of serum markers (serum CRP, ESR, procalcitonin, IL‐6, D‐Dimer, WBC, platelet count [PLT], neutrophil to lymphocyte ratio [NLR], monocyte to lymphocyte ratio [MLR], platelet to lymphocyte ratio [PLR], platelet to mean platelet volume ratio [PVR], FDP [fibrin degradation product] and Fibrinogen), 9–11,24–149 114 studies reported synovial markers (synovial WBC, PMN%, IL‐6, IL‐1β, CRP, TNF‐α, Calprotectin, and leucocyte esterase [LE] and laboratory or lateral‐flow based α‐defensin test),…”
Section: Resultsmentioning
confidence: 99%
“…Final analysis was performed on 215 articles with six additional studies searched manually, as shown in platelet to mean platelet volume ratio [PVR], FDP [fibrin degradation product] and Fibrinogen), [9][10][11] 114 studies reported synovial markers (synovial WBC, PMN%, IL-6, IL-1β, CRP, TNF-α, Calprotectin, and leucocyte esterase [LE] and laboratory or lateral-flow based α-defensin test), 10,29,31,34,36,43,49,51,52,58,59,61,62,64,65,[72][73][74]76,77,[79][80][81][84][85][86][87][88]90,95,97,99,117,118,122,124,125,127,129,132,[135][136][137][138]142,1...…”
Section: Study Selectionmentioning
confidence: 99%
“…The magnitude and the timing of peak concentrations, as well as the duration of elevation, vary between each test and type of procedure 20,21 . C‐reactive protein levels peak on postoperative day 2 and return to preoperative levels by day 21 in uncomplicated total hip arthroplasty (THA) in humans; elevations that persist beyond established acute and chronic time points are highly indicative of infection 14–24 …”
Section: Introductionmentioning
confidence: 99%
“…20,21 C-reactive protein levels peak on postoperative day 2 and return to preoperative levels by day 21 in uncomplicated total hip arthroplasty (THA) in humans; elevations that persist beyond established acute and chronic time points are highly indicative of infection. [14][15][16][17][18][19][20][21][22][23][24] Serum CRP and serum amyloid A (SAA) are reliable biomarkers of inflammation in dogs, [25][26][27][28] with some evidence that SAA is better able to differentiate between inflammatory and noninflammatory states than CRP. 29 Acute-phase proteins in dogs with postoperative orthopedic infection have been investigated previously, 30 but their clinical utility for dogs undergoing joint replacement surgery is unknown.…”
Section: Introductionmentioning
confidence: 99%